Impact of transport on arrival status and outcomes in newborns with heart disease: a low–middle-income country perspective. (9th June 2020) - Karmegaraj, Balaganesh; Kappanayil, Mahesh; Sudhakar, Abish; Kumar, Raman Krishna
Abstract: Objectives: We sought to systematically study determinants of "clinical status at arrival after transport" of neonates with CHD and its impact on clinical outcomes in a low- and middle-income country environment. Methods and results: Consecutive neonates with CHD (n = 138) transported (median distance 138 km; 5–425 km) to a paediatric cardiac programme in Southern India were studied prospectively. Among 138 neonatal transports, 134 were in ambulances. Four neonates were transported by family in private vehicles; 60% with duct-dependent circulation (n = 57) were transported without prostaglandin E1. Clinical status at arrival after transport was assessed using California modification of TRIPS Score (Ca-TRIPS), evidence of end-organ injury and metabolic insult. Upon arrival, 42% had end-organ injury, 24% had metabolic insult and 36% had Ca-TRIPS Score >25. Prior to surgery or catheter intervention, prolonged ICU stay (>48 hours), prolonged ventilation (>48 hours), blood stream sepsis, and death occurred in 48, 15, 19, and 3.6%, respectively. Ca-TRIPS Score >25 was significantly associated with mortality (p = 0.005), sepsis (p = 0.035), and prolonged ventilation (p < 0.001); end-organ injury with prolonged ICU stay (p = 0.031) and ventilation (p = 0.045); metabolic insult with mortality (p = 0.012) and sepsis (p = 0.015). Fifteen babies needed only medical management, 10 received comfort care (due to severe end-organ injury in 3), 107 underwent cardiac surgery (n = 83) or catheter intervention (n = 24), with a mortality of 6.5%. Clinical status at arrival after transport did not impact post-procedure outcomes. Conclusion: Neonates with CHD often arrive in suboptimal status after transport in low- and middle-income countries resulting in adverse clinical outcomes. Robust transport systems need to be integrated in plans to develop newborn heart surgery in low- and middle-income countries.